Setting Priority for Improvement of Yogurt Production Process Using Quality Function Deployment (QFD) on Household Industry (IRT) X, Sumedang - Totok Pujianto; Desy Amalia; Handarto Handarto (APTA and DTIP FTP UGM, 2017)
This study aims to determine the priority of the yogurt production process improvement by the household industry (Industri Rumah Tangga = IRT) X, so that the products according to the needs and expectations of consumers. This is done by applying the method of Quality Function Deployment (QFD) which aims to find the gap between the needs and expectations of consumers by way of an industry to fulfill it from the side of the two basic components of technology: techno-ware and human-ware. The competency gap is analyzed through: (1) the relation between the requirements of the yogurt product and the production process; (2) the importance weight of both of them based on techno-ware and human-ware aspects; and (3) assessment of competency level and (4) assessment of industrial competency level based on techno-ware and human-ware aspects. The study involved 203 respondents in obtaining information about the needs and expectations of consumers in yogurt products (yogurt product requirements). Depth analysis of the yogurt production process was done by direct observation and interviews. Assessment of product requirements and production process in the form of a matrix involving 4 experts. Product requirements based on the results of this study were (1) the benefits of yogurt to help facilitate the digestive system; (2) the legality of (management of legality, halal certification, food safety in form of the acquisition of a number MD); (3) volume per pack of 250 ml; (4) price per pack was IDR 6,001 - 9,000; (5) type is strawberry flavor; (6) degree of acidity is medium; (7) smooth texture; (8) viscosity is medium; (9) type of packaging is plastic bottles; (10) the information listed on the packaging consists of the manufacture of packaging labels, expiration date, legality, brand, composition, nutritional value information, net weight, description of taste, production code, and manufacturers; and (11) additional pieces of fruit. The results of this study indicate that the company need to complete or replace some of the production facilities, improve the ability of workers, and improve the hygiene of workers and production facilities. A major reshuffle is necessary to eliminate the gaps in the following sequence of actions: (1) complete and / or replace some facilities of yogurt production processes adapted to financial circumstances; (2) provide guidance and monitoring of workers to perform all activities in the process of producing yogurt correctly; (3) adding to the completeness of workers with hygiene equipment; And (4) place the production facility in accordance with the sequence of processes.